A case of Fryns syndrome. Issue 1 (February 1986) - Young, I D; Simpson, K; Winter, R M
Abstract : A case of Fryns syndrome is presented. Characteristic features of this lethal autosomal recessive disorder include corneal clouding, camptodactyly with hypoplastic nails, and abnormalities of the diaphragm.